The multifaceted nature of retinoid transport and metabolism - Li, Yang (AME Publishing Company, 2014)
Since their discovery over a century ago, retinoids have been the most studied of the fat-soluble vitamins. Unlike most vitamins, retinoids are stored at relatively high concentrations in the body to buffer against nutritional insufficiency. Until recently, it was thought that the sole important retinoid delivery pathway to tissues involved retinol bound to retinol-binding protein (RBP4). More recent findings, however, indicate that retinoids can be delivered to tissues through multiple overlapping delivery pathways, involving chylomicrons, very low density lipoprotein (VLDL) and low density lipoprotein (LDL), retinoic acid bound to albumin, water soluble β-glucuronides of retinol and retinoic acid, and provitamin A carotenoids. This review will focus on explaining this evolving understanding of retinoid metabolism and transport within the body.